Molecular mechanism of pH-dependent substrate transport by an arginine-agmatine antiporter - Wang, Sheng (National Academy of Sciences, 2014)
Enteropathogenic bacteria, exemplified by Escherichia coli, rely on acid-resistance systems (ARs) to survive the acidic environment of the stomach. AR3 consumes intracellular protons through decarboxylation of arginine (Arg) in the cytoplasm and exchange of the reaction product agmatine (Agm) with extracellular Arg. The latter process is mediated by the Arg:Agm antiporter AdiC, which is activated in response to acidic pH and remains fully active at pH 6.0 and below. Despite our knowledge of structural information, the molecular mechanism by which AdiC senses acidic pH remains completely unknown. Relying on alanine-scanning mutagenesis and an in vitro proteoliposome-based transport assay, we have identified Tyr74 as a critical pH sensor in AdiC. The AdiC variant Y74A exhibited robust transport activity at all pH values examined while maintaining stringent substrate specificity for Arg:Agm. Replacement of Tyr74 by Phe, but not by any other amino acid, led to the maintenance of pH-dependent substrate transport. These observations, in conjunction with structural information, identify a working model for pH-induced activation of AdiC in which a closed conformation is disrupted by cation–π interactions between proton and the aromatic side chain of Tyr74.